A comparative study of online review management in hospitality services. (4th January 2021) - Niu, Run H.; Fan, Ying
Managing online reviews has become an essential task for managers thanks to the profound impact of customer online reviews on hospitality services. Multinational hospitality services face mounting challenges of managing online reviews posted by domestic and international customers when operating and competing in different countries. Based on a comparative case study, this paper provides a comprehensive understanding of online review management practices in the hospitality industries in the USA and China. The study develops a conceptual framework for key online review management practices and identifies the similarities and differences of these key practices between the USA and China. The key practices set the groundwork for developing an integrated framework for evaluating online review management practices. The comparison provides guidelines for multinational companies to manage online review management practices in different countries when competing with other multinational or domestic companies.